Hubungan Pelayanan Kesehatan dan Jenis Metode Kontrasepsi dengan Kepuasan Akseptor KB di Kelurahan Rempang Cate Wilayah Kerja Puskesmas Rempang Cate - Nahrul Heza Nanda; Nelli Roza; Rofiqo Larasati Philip (Pusat riset dan Inovasi Nasional, 2025)
Background: The government has implemented a program to increase the use of Long-Term Contraceptive Methods (LTCM) with a national target of 28% in 2024; however, the current achievement is only 23.5%. Batam City is one of the government’s priority areas to increase contraceptive use, but several factors, such as satisfaction levels and health service quality, are still considered low. Objective: This study aims to analyze the relationship between health services and types of contraceptive methods with the satisfaction level of family planning acceptors in Rempang Cate Sub-district, Batam City. Methods: This quantitative research used an analytical observational design with a cross-sectional approach. The population consisted of fertile couples (PUS) in Rempang Cate Village. A total of 34 respondents were selected using purposive sampling techniques. Data were collected through observation sheets and questionnaires and analyzed using the Chi-square test. Results: The findings show that among 17 acceptors with poor health services, only 1 (5.9%) was satisfied, while among those with good health services, 16 were satisfied, and 1 (5.9%) was dissatisfied. Statistical analysis using SPSS showed a p-value = 0.000 (p < 0.05), indicating a significant relationship between health services and family planning acceptor satisfaction. Conclusion: There is a significant relationship between health service quality and the satisfaction of family planning acceptors, but no significant relationship was found between the type of contraceptive method and satisfaction.